2021
DOI: 10.1371/journal.pone.0255676
|View full text |Cite
|
Sign up to set email alerts
|

Trends of adult height in India from 1998 to 2015: Evidence from the National Family and Health Survey

Abstract: Aim The aim of the study is to investigate the trends in adult height between two consecutive surveys of NHFS and explore differences across variables such as gender, wealth, social groups etc. Methods We used the NFHS-II (1998–99), NFHS–III (2005–2006) and NFHS-IV (2015–16) (all three for women and last two for men) data to examine the trends in average height. Comparison was done between the two age strata of 15–25 and 26–50 years, across both male and female, to assess the trends. Results Between NFHS-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Our models were informed by various district-specific covariates, among which the literacy rate (LR) and the proportion of working population (WP) had significant negative influences respectively on a district’s food insecurity. Interestingly, while the share of LR in the EIGP is lower than the national average, other recent, independent studies on malnutrition in India also provide evidence in the same direction [ 50 ]. In small area literature [ 23 ], two standard types of validation are conducted: internal and external.…”
Section: Discussionmentioning
confidence: 85%
“…Our models were informed by various district-specific covariates, among which the literacy rate (LR) and the proportion of working population (WP) had significant negative influences respectively on a district’s food insecurity. Interestingly, while the share of LR in the EIGP is lower than the national average, other recent, independent studies on malnutrition in India also provide evidence in the same direction [ 50 ]. In small area literature [ 23 ], two standard types of validation are conducted: internal and external.…”
Section: Discussionmentioning
confidence: 85%
“…Studies on adult height in India also showed that the average height of those belonging to Scheduled Tribe and Scheduled Caste categories were shorter than those of higher castes. Over time, the average height of Indians for both males and females has improved, but the improvement was higher among males than females [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Height differences are related to multiple factors such as the pituitary-growth hormone axis (growth hormone [34][35][36] , etc. ), genes 37,38 , society, and environment 39 , while liver stiffness is positively correlated with visceral fat and ALT, γ-GT and AST, and fat mass 40 . We hypothesize that this height disparity affects the liver in a variety of ways, which comprises size, nutritional status 41 , blood supply, and susceptibility to external factors that damage the liver, resulting in changes to the liver's texture (fatty changes, brous changes, etc.…”
Section: Discussionmentioning
confidence: 99%